Reflective Journaling to Assure Learning in the Affective Domain. (August 2022) - Deepa, R.; Mansurali, A.
The case presents reflective journaling as an effective tool to assess higher-order learning outcomes. There are two predominant approaches to learning namely surface and deep learning. Surface learning stops with the acquisition, remembering, reproducing and using the knowledge whereas deep learning culminates in development or change by enabling the learner to evaluate and create. The case describes a challenge encountered in the course 'Emotional Intelligence for Managers', which is a part of the Master of Business Administration programme in a leading business school in South India. In this course, learning happens in the affective domain and should culminate in a change in attitude or behaviour of the learner, who in turn should be capable of applying the learning to different situations. Standardized assessment components such as quizzes, viva and written tests cannot be used to assess this higher conception of learning and, hence, the instructor chose journal writing to assure learning and attainment of higher-order learning outcomes. Journal writing is a process in which learners record events, their responses to those events, and their reflections on the responses. This facilitates critical thinking and motivates deep learning. The case demonstrates the use of reflective journaling as a tool to assess learning in the affective domain and also shares evidence of the positive outcomes of reflective journaling. The case also serves as a blueprint to foster and assess deep learning in the classrooms.